The public policy of Islamic Banking in Algeria: An examination of the governing legal and legislative framework - Reguieg, Farouk; Boudache, Siham (The International tax journal, 2025)
This study focuses on analysing the legal and legislative framework governing Islamic banking activities in Algeria, with particular emphasis on shedding light on the public policy adopted in this regard, especially as this field has, for more than two decades, experienced a legal and legislative gap that has generated deficiencies in public policy and adversely affected the quality of its outputs. The study concludes with a set of findings, the most salient of which is that the issuance of statutes and regulatory instruments governing the operation of Islamic banks constitutes a positive step towards strengthening the sector. Nevertheless, the current legal reform efforts remain insufficient to develop Islamic banking in a manner that addresses existing challenges and reduces the marked lag afflicting this industry, particularly in light of the continued absence of a comprehensive regulatory and legal framework that supports the work of Islamic financial institutions in Algeria.